10(n+1)+5(n)+25(n-1)=265

Simple and best practice solution for 10(n+1)+5(n)+25(n-1)=265 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10(n+1)+5(n)+25(n-1)=265 equation:


10(n+1)+5(n)+25(n-1)=265

We simplify the equation to the form, which is simple to understand
10(n+1)+5(n)+25(n-1)=265

Reorder the terms in parentheses
+(+10n+10)+5*(n)+25*(n-1)=265

Remove unnecessary parentheses
+10n+10+5+*(+n+)+25+*(+n-1+)=+265

Reorder the terms in parentheses
+10n+10+(+5n)+25*(n-1)=265

Remove unnecessary parentheses
+10n+10+5n+25+*(+n-1+)=+265

Reorder the terms in parentheses
+10n+10+5n+(+25n-25)=265

Remove unnecessary parentheses
+10n+10+5n+25n-25=+265

We move all terms containing n to the left and all other terms to the right.
+10n+5n+25n=+265-10+25

We simplify left and right side of the equation.
+40n=+280

We divide both sides of the equation by 40 to get n.
n=7

See similar equations:

| x/(0,5-x)=2.43 | | x+1.67x=5.00 | | 10(3n+4)+5(n)=215 | | 2x+8=9x-27 | | (-15)-(-18)/3= | | 3ln(5x)+7=22 | | 5(n)+25(3n)=160 | | (-15)-(-18)/3 | | 6x-42x+62=-10 | | x+1.13x=500000 | | 0=x-2*x*ln(x) | | X^2+15x-6=10x | | 50(h)+5(3h)+25(20-4h)=360 | | 10x+20y+65= | | 10(d)+5(120-d)=1000 | | 25x+5=18x-9 | | 10(d)+25(92-d)=1400 | | 10(d)+25(932-d)=1400 | | 10(d)+5(21-d)=165 | | 2u+14=46 | | 10(d)+5(d+2)+25(d+2+3)=335 | | M^2+19m+34= | | 9x-3=10x+3 | | 10(d)+5(2d)+50(2d+5)=610 | | 2N+19=2(2(10))+1 | | 2N+19=2(2(4))+1 | | 2x+10=9x-18 | | 8v+26=(-4v-6)-6 | | 10(d)+5(d+2)=115 | | 2N+19=2(20)+1 | | 2N+19=2(9)+1 | | 4+10=3-2 |

Equations solver categories